Filogenia de los piojos (Insecta: Anoplura) de los monos del Viejo Mundo (Catarrhini) - Retana Salazar, Axel P (1994)
The genera Pediculus and Pthirus were studied cladistically, although the genus Pedicinus was also taken into account. Morphological characters from the literature, and sorne established through direct study were analyzed. Using five methods of cladistic analysis, one most parsimonious tree with a cj.= 0.84 and a length of 38 was obtained «Pedicinus}+(Paenipediculus+(Parapediculus+(Pediculus humanus capitis+Pediculus humanus humanus). A novelty of this study is the inclusion of the subgenus